2019
DOI: 10.1055/s-0039-1692406
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Thyroid Stimulating Hormone Levels between Differentiated Carcinoma and Benign Enlargement

Abstract: Introduction  Papillary and follicular thyroid carcinoma are common head and neck cancers. This cancer expresses a thyroid stimulating hormone (TSH) receptor that plays a role as a cancer stimulant substance. This hormone has a diagnostic value in the management of thyroid carcinoma. Objective  The present study aimed to determine the difference in TSH levels between differentiated thyroid carcinoma and benign thyroid enlargement. Methods  The present research design was a case-control study. The subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, there were no studies designed to evaluate the responses of TSH-R to administering TSH or recombinant human TSH (rhTSH) into tissues containing of benign or malignant thyrocytes. This gap contrasts with the results of intensive research on TSH levels in serum [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 89 , 90 , 91 ], circadian clock genes expression [ 2 , 39 , 64 , 70 , 103 , 104 , 105 ] in thyrocytes, and TSH-R gene activation at thyrocytes’ membrane [ 107 , 108 , 109 , 110 , 111 , 112 , 114 , 115 , 116 , 117 , 118 , 119 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…However, there were no studies designed to evaluate the responses of TSH-R to administering TSH or recombinant human TSH (rhTSH) into tissues containing of benign or malignant thyrocytes. This gap contrasts with the results of intensive research on TSH levels in serum [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 89 , 90 , 91 ], circadian clock genes expression [ 2 , 39 , 64 , 70 , 103 , 104 , 105 ] in thyrocytes, and TSH-R gene activation at thyrocytes’ membrane [ 107 , 108 , 109 , 110 , 111 , 112 , 114 , 115 , 116 , 117 , 118 , 119 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 80%
“…Results of intensive testing of TSH concentrations in serum suggested the increase of the risk of malignancy in thyroid nodules in parallel with the increase of these concentrations [ 73 ]. The results of published studies suggested that the likelihood of thyroid cancer increased with increase of serum TSH concentrations [ 74 ], that patients with high serum TSH levels had a significantly higher risk of differentiated carcinoma than patients with low levels [ 75 ], that higher TSH concentrations, even within the normal range, were associated with a subsequent diagnosis of thyroid cancer in individuals with thyroid abnormalities [ 76 ], that the levels of serum TSH in the group with differentiated thyroid cancer was significantly increased compared with that in the benign TN group [ 77 ], and that TSH levels in patients of stage 3 were significantly higher than those in patients in stages 2 and 1 [ 78 ], etc. Therefore, it was concluded that levels of this hormone in serum might have a diagnostic value in the preoperational management of thyroid carcinoma [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with high TSH levels have a higher risk of differentiated carcinoma than patients with low TSH levels. Thyroid-stimulating hormone levels are an independent predictor for the diagnosis of thyroid malignancies in patients with thyroid gland enlargement ( 27 ). The role of hyperthyroidism in the production of thyroid cancers is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pathogenesis of TA is not completely clear, but relevant studies show that it may be closely related to radiation exposure, genetics, gender, thyroid-stimulating hormone stimulation, etc., with a high incidence in clinical practice, affecting the quality of life of human beings (10). If TA does not receive timely diagnosis and treatment, it may cause malignant transformation of tumor and hyperthyroidism, which increases the difficulty of clinical treatment (11,12). As the best diagnostic method of TA, needle aspiration cytology has high accuracy, but it also has certain trauma.…”
Section: Analysis Of the Value Of The Combined Detection Of Serum Tg ...mentioning
confidence: 99%